Bacterial endophthalmitis with lens capsule rupture and retinal detachment: A case report of Rhizobium radiobacter infection - Nao Mizutani; Kumiko Kato; Yuzen Kashima; Yoshitsugu Matsui; Masahiko Sugimoto; Hisashi Matsubara; Mineo Kondo (American Journal of Ophthalmology Case Reports)
Purpose: To report our findings in a rare case of unilateral endophthalmitis caused by Rhizobium radiobacter in a healthy young man complicated by a rupture of the lens capsule and a rhegmatogenous retinal detachment (RRD). Observations: A 22-year-old Cambodian man presented with recurrent blurry vision in the left eye, following a two-year history of recurrent uveitis initially responsive to corticosteroid treatment. However, during the second recurrence, corticosteroids failed to control the inflammation. At our initial examination, non-granulomatous keratic precipitates, posterior synechiae, and vitreous opacities were observed. Polymerase chain reaction (PCR) of the aqueous humor identified bacterial DNA leading to a suspicion of bacterial endophthalmitis. Vitreous surgery revealed a lens capsule rupture and a giant retinal tear. Retinal photocoagulation and silicone oil tamponade were performed to reattach the retina. Given his occupation at a construction site, ocular trauma was considered. However, preoperative examination and intraoperative findings revealed no evidence of intraocular foreign bodies. Cultures of the vitreous fluid detected R. radiobacter. Targeted antibiotic therapy with topical levofloxacin and systemic ciprofloxacin was administered, and the decimal best-corrected visual acuity improved to 1.2 two months post-treatment. Importance and conclusion: This case highlights the diagnostic and therapeutic challenges posed by rare pathogens such as R. radiobacter. Clinicians should be aware of bacterial causes in atypical uveitis particularly in patients refractory to conventional therapy.